Analisis Sistem Penangkal Petir pada Light Rail Transit (LRT): (Studi Kasus Project LRT Jakarta Fase 1B) - Feriyawan Feriyawan; Seflahir Dinata; Jamal A Rachman Saprin; Angga Septian MN (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
Indonesia is a country with high lightning strike intensity, making lightning protection systems critically important, especially for public infrastructure such as Light Rail Transit (LRT). This research aims to analyze the lightning protection system implemented in the Jakarta LRT Phase 1B Project, particularly in the station areas and railway lines. The methods used include field observation, literature study, interviews, and technical analysis using the rolling sphere method, protective angle method, and mesh method to determine the coverage of protected areas. In addition, an evaluation of the grounding system was conducted to ensure the safe discharge of lightning currents into the earth. The analysis results show that the lightning protection system applied complies with PUIPP and IEC 62305-1 standards and is capable of protecting signaling and telecommunication equipment from lightning risks. The combination of the three protection methods provides comprehensive coverage for LRT structures. The grounding system design also meets the standard resistance requirement (< 5 Ohms), ensuring operational safety and protecting critical equipment. Furthermore, the study highlights the importance of integrating lightning protection with other safety systems such as fire protection and electrical surge protection, as lightning can cause cascading failures that disrupt railway operations. Proper maintenance and periodic testing of grounding resistance are also necessary to ensure long-term reliability. In addition, the Faraday cage principle applied to train cars contributes to passenger safety by preventing lightning currents from penetrating the cabin interior. This research is expected to serve as a reference for developing lightning protection systems in similar infrastructure projects, especially in regions with high lightning density. By applying international standards and comprehensive protection methods, the Jakarta LRT demonstrates how modern urban transportation can operate safely despite extreme weather risks.